10
$\begingroup$

I'm solving the functional equation $f(x+y)=f(x)f(y)$ and I know that I have a continuous function $f:[0,\infty\rangle \to \langle 0,\infty\rangle$ s.t. $f(0)=1$. In one of the steps, I want to show that the limit $$\lim_{x \rightarrow 0} \frac{f(x)-1}{x}$$ exists and is finite?

I'm just looking for a hint.

$\endgroup$
  • $\begingroup$ I clarified your title which I thought was a bit misleading before. $\endgroup$ – 6005 Aug 7 '16 at 11:02
  • 1
    $\begingroup$ @Med The limit can still exist at $0$ if $f$ is defined only on nonnegative values. $\endgroup$ – smcc Aug 7 '16 at 11:13
  • 1
    $\begingroup$ @Med Pretend that it says $\lim_{x\to 0^+}$. Depending on your concrete definition of limit, is actually not a problem at all. $\endgroup$ – Arthur Aug 7 '16 at 11:17
  • 1
    $\begingroup$ If $f$ is allowed to take negative values, things get difficult. Are you sure that $f$ isn't (strictly) positive? $\endgroup$ – Alex M. Aug 7 '16 at 11:29
  • 1
    $\begingroup$ @AlexM. The function cannot take negative values: $f(x)=f(x/2+x/2)=(f(x/2))^2\ge0$. $\endgroup$ – egreg Aug 8 '16 at 9:40
14
$\begingroup$

The following is a solution of the functional equation $$f(x + y) = f(x)f(y)$$ for all real $x, y$ in a more general setting where $f:\mathbb{R}\to \mathbb{R}$ is a function which is continuous everywhere.


One solution (the trivial one) is that $f(x) = 0$ for all $x$ and then the limit $\lim_{x \to 0}\dfrac{f(x) - f(0)}{x} = 0$ exists.

Let's us then suppose that $f(x)$ is not identically zero. So there is a number $a$ such that $f(a)\neq 0$. Now $f(a) = f(a/2)f(a/2) \geq 0$ so $f(a) > 0$. Now we can see that $$f(a) = f(a + 0) = f(a)f(0)$$ so that $f(0) = 1$.

Note further that if $f(b) = 0$ then $f(x) = f(b)f(x - b) = 0$ for all $x$. Hence it follows that $f(x) \neq 0$ for all $x$ and by the reasoning in last paragraph $f(x)$ is positive everywhere. Next let $f(1) = k$ where $k > 0$ and then I will show that the behavior of $f$ crucially depends on $k$. Note that by simple alegbraic arguments and using the equation $f(x)f(y) = f(x + y)$ we can show that $f(x) = k^{x}$ when $x$ is rational. And if $k = 1$ then $f(x) = 1$ for all rational $x$ and via continuity $f(x) = 1$ for all $x$. Thus if $k = 1$ the desired limit in question exists and is equal to $0$.

It is important to observe that the value of $f(1) = k$ determines the function uniquely. Thus if $g, h$ are two non-trivial continuous solutions of the functional equation $f(x + y) = f(x)f(y)$ then $g, h$ are positive and hence the function $F$ given by $F(x) = g(x)/h(x)$ is well defined and continuous. Moreover $F$ is also a solution of the functional equation. If $g(1) = h(1)$ then $F(1) = 1$ and by last paragraph $F(x) = 1$ for all $x$ and hence if $g(1) = h(1)$ then $g(x) = h(x)$ for all $x$. Thus we see that a continuous non-trivial solution of $f(x + y) = f(x)f(y)$ is uniquely determined by the value $k = f(1)$.

Next let $k > 1$. Using some amount of algebraic manipulation we can show that $$\frac{f(x) - f(0)}{x} < \frac{f(y) - f(0)}{y}$$ for rational $x, y$ with $0 < x < y$. If $x, y$ are real numbers with $0 < x < y$ then we can choose sequences of rationals $x_{n}, y_{n}$ such that $x_{n} \to x, y_{n} \to y$. Let $u, v$ be rationals with $0 < x < u < v < y$ and then after a certain value of $n$ we will have $0 < x_{n} < u < v < y_{n}$ and therefore $$\frac{f(x_{n}) - f(0)}{x_{n}} < \frac{f(u) - f(0)}{u} < \frac{f(v) - f(0)}{v} < \frac{f(y_{n}) - f(0)}{y_{n}}$$ and on taking limits as $n \to \infty$ we get $$\frac{f(x) - f(0)}{x} \leq \frac{f(u) - f(0)}{u} < \frac{f(v) - f(0)}{v} \leq \frac{f(y) - f(0)}{y}$$ Here we have used continuity of $f$. Note that from the above we get the desired equation $$\frac{f(x) - f(0)}{x} < \frac{f(y) - f(0)}{y}$$ for all real $x, y$ with $0 < x < y$ under the assumption that $f(1) = k > 1$. So we have established that the function $g(x) = \dfrac{f(x) - f(0)}{x}$ is strictly increasing in $(0, \infty)$.

We next need to show that $g(x) \geq 0$ for all $x > 0$. Again let $x_{n}$ be a sequence of rationals tending to $x$. Then $x_{n} > 0$ after a certain value of $n$ and then $$g(x_{n}) = \frac{f(x_{n}) - f(0)}{x_{n}} = \frac{k^{x_{n}} - 1}{x_{n}} > 0$$ because $k > 1$. Taking limits as $n \to \infty$ and via continuity of $g$ we get $g(x) \geq 0$ for all $x$. It follows now that $\lim_{x \to 0^{+}}g(x)$ exists.

We will show that $\lim_{x \to 0^{-}}g(x)$ also exists and is same as $\lim_{x \to 0^{+}}g(x)$. Clearly we have \begin{align} L &= \lim_{x \to 0^{-}}g(x)\notag\\ &= \lim_{x \to 0^{-}}\frac{f(x) - f(0)}{x}\notag\\ &= \lim_{t \to 0^{+}}\frac{f(-t) - f(0)}{-t}\notag\\ &= -\lim_{t \to 0^{+}}\frac{f(-t + 0) - f(-t + t)}{t}\notag\\ &= -\lim_{t \to 0^{+}}f(-t)\cdot\frac{f(0) - f(t)}{t}\notag\\ &= f(0)\lim_{t \to 0^{+}}\frac{f(t) - f(0)}{t}\notag\\ &= \lim_{x \to 0^{+}}\frac{f(x) - f(0)}{x}\notag \end{align} It follows that $\lim_{x \to 0}g(x)$ exists. If $0 < k < 1$ then also the same result holds but then $g(x)$ may be negative and you need to establish the bound that $g(x) \geq (k - 1)/k$ with more algebraic manipulation.

The value of the limit $$\lim_{x \to 0}\frac{f(x) - f(0)}{x}$$ crucially depends on $k = f(1)$ and thus defines a function of $k$ say $L(k)$. We have seen that for $k = 1$ we have $L(k) = 0$ and with some effort we can show that $L(x)$ is a continuous and differentiable function of $x$ on $(0, \infty)$ with the property that $L(xy) = L(x) + L(y)$ and $L'(x) = 1/x$ (you should try to prove these facts about $L$) and at this point you understand that $L(x)$ is more popularly known and written as $\log x$.


Note that in the above we have proved that $f'(0)$ exists and using functional equation $f(x)f(y) = f(x + y)$ we can show easily that $f'(x) = f(x)f'(0)$. Thus using the fact that $f$ is continuous and $f(x + y) = f(x)f(y)$ we have shown that $f$ is differentiable for all $x$. Going a step further (and also to summarize) we can show that

If $f$ is continuous at any single point say $a$ and $f(x + y) = f(x)f(y)$ then $f$ is continuous and differentiable everywhere with $f'(x) = f(x)f'(0)$ and leaving aside the trivial solution $f(x) = 0$ everywhere the value of $f'(0)$ is a function of $f(1) = b$ so that $f'(0) = L(b)$ and $L$ is continuous and differentiable on $(0, \infty)$ and $L'(x) = 1/x$.

$\endgroup$
  • $\begingroup$ that's a great in depth solution $\endgroup$ – MathIsTheWayOfLife Aug 8 '16 at 9:23
  • 1
    $\begingroup$ @MathIsTheWayOfLife: A shortcut is that $f(x) = k^{x}$ for rational $x$ by continuity $f(x) = k^{x}$ for all $x$. However here we skip the justification of the part that $k^{x}$ is something which can be defined for all real $x$ in manner that it is continuous and differentiable (and this is difficult if you don't want to bring $e$ and $\log$ in picture). Hence I gave an indepth answer which does not use the theory of real exponents and instead relies on rational exponents. $\endgroup$ – Paramanand Singh Aug 8 '16 at 9:26
8
$\begingroup$

You can easily check that $f(\frac pq) = f(1)^{\frac pq} \; \forall \frac pq \in \Bbb Q$, so $\left.f\right|_{\Bbb Q}$ is just an exponential.

Now, since we know the function is continous and $\Bbb Q$ happens to be dense in $\Bbb R$ we can state that $f(x) = f(1)^x \; \forall x$, and now you just have to compute the derivative of some $a^x$, which we know is differentiable at $x=0$.

$\endgroup$
  • 1
    $\begingroup$ Care must be taken: if $f(x) < 0$, then what is $f(x)^{\frac 1 n}$ for $n \in \Bbb N$? $\endgroup$ – Alex M. Aug 7 '16 at 11:26
  • 2
    $\begingroup$ Then $f(x+y) = f(x)f(y)$ wouldn't hold by continuity $\endgroup$ – cronos2 Aug 7 '16 at 11:40
  • 4
    $\begingroup$ @AlexM $f(x) = f\left(\tfrac{x}{2} + \tfrac{x}{2}\right) = f\left(\tfrac{x}{2}\right)f\left(\tfrac{x}{2}\right) \ge 0$. $\endgroup$ – 6005 Aug 8 '16 at 1:48
  • 1
    $\begingroup$ @cronos2 I didn't follow your argument for why $f(x) \ge 0$ in that comment. $\endgroup$ – 6005 Aug 8 '16 at 1:50
  • $\begingroup$ @6005 it goes more or less like $f(0) = 1, f(x) < 0 \implies \exists y / f(y) = 0$ and now try to find some $x'$ in between that must be positive and negative, which you found in a much simpler way. $\endgroup$ – cronos2 Aug 8 '16 at 9:13
5
$\begingroup$

To get around the fact that you can't differentiate $f$ (yet), we'll integrate it! Define $F$ to be the following primitive of $f$

$$F(x) = \int_0^x f(t) \, dt$$

Integrating $f(x+y) = f(x)f(y)$, with regards to $x$, between $0$ and $1$ (actually you may chose any non zero number here), we get

$$F(y+1) - F(y) = f(y)F(1)$$

Since $f$ is positive, $F(1) \ne 0$, and we get

$$f(y) = \frac{F(y+1)-F(y)}{F(1)}$$

Now the right hand side is clearly $\mathcal{C}^1$, so $f$ is $\mathcal{C}^1$ too.

$\endgroup$
  • 1
    $\begingroup$ Simple and elegant. Very smart use of integration. +1 $\endgroup$ – Paramanand Singh Aug 10 '16 at 16:27

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.